2010
DOI: 10.1177/1082013210367559
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Nutritional and Antioxidant Properties of Tempeh Flour from Common Bean ( Phaseolus vulgaris L.)

Abstract: The effects of solid state fermentation (SSF) on physicochemical, nutritional and antioxidant properties of common bean flour were studied. SSF increased protein content (21.7%) and decreased lipids (-38.4%), carbohydrates (-3.5%) and phytic acid (-58.3%). Fermented (tempeh) flour showed higher dispersability, lower water solubility index and pH than unfermented flour. Fermentation also increased an average of 0.21 g/100 g protein, six of the essential amino acids (EAAs), including total sulfur (Met + Cys), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 29 publications
4
43
2
2
Order By: Relevance
“…What is more important, tempe is characterized by the favourable nutritional composition and a low level of antinutrients (Nout and Kiers, 2005). The substrate for tempe-type processing are usually soybeans, but other plant materials may also be used (Granito et al,2005;Reyes-Bastidas et al,2010;Stodolak et al 2013). When common beans are used as the fermentation substrate, the important advantage may be the decomposition of flatulence-producing α-galactosides, which limit the consumption of common beans in Western countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…What is more important, tempe is characterized by the favourable nutritional composition and a low level of antinutrients (Nout and Kiers, 2005). The substrate for tempe-type processing are usually soybeans, but other plant materials may also be used (Granito et al,2005;Reyes-Bastidas et al,2010;Stodolak et al 2013). When common beans are used as the fermentation substrate, the important advantage may be the decomposition of flatulence-producing α-galactosides, which limit the consumption of common beans in Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…Dark common bean is also considered functional food (Vadivel et al, 2011) due to the high level of phenolic compounds present in the seed coat (Boateng et al, 2008).However, processes usually applied in order to prepare dry beans for the consumption (soaking and cooking) significantly diminish the antioxidant activity of the seeds, therefore decreasing their functional properties (Xu and Chang, 2009 (Granito et al,2005;Reyes-Bastidas et al,2010;Stodolak et al 2013). When common beans are used as the fermentation substrate, the important advantage may be the decomposition of flatulence-producing α-galactosides, which limit the consumption of common beans in Western countries.…”
mentioning
confidence: 99%
“…Previous studies of SSB with cereals and legumes have reported a significant increase in total protein content during the fermentation [1,12,25]. Sánchez-Magaña et al [26] reported that the increase in protein content reflects the decrease of other constituents, which might have been lost by leaching during the initial steps of SSB or might have been consumed by the fungus for its growth.…”
Section: Chemical Composition and Nutritional Properties Of Bqpmf Andmentioning
confidence: 99%
“…The bioprocessed quality protein maize (BQPMF) and common bean (BCBF) were prepared according Cuevas-Rodríguez et al [1] and Reyes-Bastidas et al [12], respectively, with modifications. Preliminary studies were realized to determinate the optimal fermentation temperature and time [15].…”
Section: Bioprocessing Of Quality Protein Maize and Common Beanmentioning
confidence: 99%
See 1 more Smart Citation